Earth Observation in support of sustainable mining by the Geological Surveys of Europe [Comunicação oral] - Kopačková, Veronika (2022)
ABSTRACT: Current and emerging Earth Observation (EO) technologies have the potential to provide regular top- surface compositional information with a high temporal rate and at high spatial resolution. Earth Observation working group (EOEG) under the EuroGeoSurveys (EGS) has been working on a topic how different type of EO data can be utilized to assess mineral resources as well as to monitor mining impacts and other anthropogenic hazards. Since 2016 the group has been contributing to the global GEO network with the GEO Community Activity (CA) entitled as “Earth Observations for Geohazards, Land Degradation and Environmental monitoring” investigating the feasibility to develop new applications or monitoring systems. Diverse Earth Observation data integration and utilization of the new generation satellite data (e.g., Copernicus data, EnMap) belongs to key topics the expert group has been working on. In addition, through this Community of Activity EOEG is sharing software tools, capacities and knowledge on the exploitation of Copernicus data for geological and anthropogenic hazard assessment and for environmental/mineral mapping. In our presentation diverse case studies will be presented showing how high spectral resolution Earth Observation data can be employed for mineral mapping and assessing environmental impacts of mining including vegetation stress. Moreover, the free toolbox – QUANTools – will be presented allowing to process hyperspectral data for mineral mapping and classification. One of the biggest advantages when using this toolbox is the fact that no prior definition of the endmembers is required, this is a requested routine used for all widely-used spectral mapping techniques. This is indeed a big advantage. As a result, it can increase time/cost efficiency as the validation samples can be collected after image classification targeting, specifically, the identified surface variability (e.g., mapped classes). In the context of new state-of-art satellite sensors and the COPERNICUS program we will also demonstrate how Sentinel-1, Sentinel-2 and WorldView3 data can be used for monitoring of mining impacts (e.g., mine stability, Acid Mine Drainage mapping).